Effect of Application of Model for Inclusive and Compulsory Participation Strategy for Teaching and Learning Mathematics on Students’ Learning Outcomes - Etukudo, Udobia Elijah Etukudo; Eze, Foluke Bosede (International Journal of Research in Mathematics Education, 2024)
Inclusive and compulsory participation strategy of teaching mathematics is designed to ensure that all the learners and the teacher are involved in the teaching and learning process. A pretest, posttest, quasi-experimental design study was carried out with 275 senior secondary school class two (SSC2) students to test the effectiveness of the model. They were divided into experimental group of 135 students, taught construction and loci using inclusive and compulsory participation strategy and control group comprising 140 students, taught the same topic using conventional strategy. The result showed that the experimental group had a mean score of 87% and standard deviation of 7% as against mean of 53% and standard deviation of 9% obtained by the control group. This give a t-test score of 34.76 which is greater than the critical value of t = 1.96 at 0.05 level of significance, implying that there existed a significant difference in the achievement, in favour of the experimental group with higher mean score. Similarly, the attitude test scores were 73% with standard deviation od 5% for the experimental group while the control group had a mean attitude score of 49% and standard deviation of 6%, giving t-test of 35.95 showing that there is a significant difference in the attitude score of the groups with the experimental group having higher mean attitude score of 73% as against 49% and standard deviation of 5% and 6% respectively obtained by the experimental and control groups. The model and its strategy is highly recommended.